Isoperistaltic gastric tube for long gap esophageal atresia (LGEA) in newborn, infants, and toddlers: a case-control study from a tertiary center - Angelo Zarfati; Angelo Zarfati; Renato Tambucci; Pietro Bagolan; Pietro Bagolan; Andrea Conforti (Frontiers Media S.A., 2023)
BackgroundLimited evidence exists about outcomes after gastric tube formation as "rescue" technique to avoid esophageal replacement in long gap esophageal atresia (LGEA). The last ERNICA Consensus Conference on the Management of LGEA has placed the techniques of gastric tubulization among the priorities for future research.AimsEvaluate personal experience with Isoperistaltic Gastric Tube (IGT) and compare its outcomes with other more popular techniques for LGEA.MethodsA case-control study has been conducted. A retrospective monocentric analysis of LGEA patients (period: 2010-19) has been conducted in all consecutive IGT patients and each of these has been type matched with two cases of LGEA treated with other techniques. The follow-up (FU) considered was 24-months.ResultsIGT and controls showed no statistically significant differences regarding preoperative variables like sex, gestational age, birth weight, syndromes, and EA type. However, IGT patients had a significantly longer esophageal GAP under boost pressure (4.5 vertebral bodies vs. 3.6, p = 0.019) at time of surgery. The analysis showed no statistical difference among the two groups about perioperative outcomes, ICU, or overall postoperative stay. No differences have been shown between IGT and controls during the follow-up regarding GERD, esophagitis, fundoplication, dysphagia, vocal cord paralysis, stenosis, and dilatations, auxologic data, need for anastomosis revision, oral aversion, and death.ConclusionsIsoperistaltic Gastric Tube is safe and effective even in LGEA patients with longer gaps, with good perioperative, post-operative and middle-term outcomes. This procedure may be considered as an alternative to avoid esophageal substitution when a primary anastomosis seems impossible for a residual gap after traction and growth techniques.